2021
DOI: 10.2174/1574885516666210719092523
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Therapy Alleviates Monosodium Urate Induced Acute Gouty Arthritis in Rats Through Inhibition of NLRP3 Inflammasome

Abstract: Background: Gout is a metabolic disease strictly related to hyperuricemia. The associated intense inflammation and pain are triggered by the deposited monosodium urate crystals (MSU) in joints. The principal therapeutic strategies of gout involve the control of hyperuricemia and anti-inflammatory medications. Objectives: This study aimed to investigate the possible beneficial effects of ozone therapy, a well-known antioxidant, and an immunomodulation, on gouty arthritis and the underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Acute episodes of gout disease are one of the most influential reasons for unfavourable health-related quality of life [ 139 , 140 , 141 ]. In a rat model, ozone therapy indicated a decrease in the degree of edematous ankle swelling, pro-inflammatory cytokines, lipid peroxidation, the nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3), procaspase-1, caspase-1, interleukin-1β synovial tissue levels with an enhancement of antioxidant defence system [ 142 ]. In other murine models, Bilge et al demonstrated that ozone therapy raises the levels of antioxidant enzymes, including oxidative shock proteins (hemo-oxygenase-1), Interleukin 4 and Interleukin 10, TGF-β, NO endorphin, adrenocorticotropic hormone (ACTH), and cortisol levels [ 141 ].…”
Section: Oxygen-ozone and Rheumatic Diseasesmentioning
confidence: 99%
“…Acute episodes of gout disease are one of the most influential reasons for unfavourable health-related quality of life [ 139 , 140 , 141 ]. In a rat model, ozone therapy indicated a decrease in the degree of edematous ankle swelling, pro-inflammatory cytokines, lipid peroxidation, the nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3), procaspase-1, caspase-1, interleukin-1β synovial tissue levels with an enhancement of antioxidant defence system [ 142 ]. In other murine models, Bilge et al demonstrated that ozone therapy raises the levels of antioxidant enzymes, including oxidative shock proteins (hemo-oxygenase-1), Interleukin 4 and Interleukin 10, TGF-β, NO endorphin, adrenocorticotropic hormone (ACTH), and cortisol levels [ 141 ].…”
Section: Oxygen-ozone and Rheumatic Diseasesmentioning
confidence: 99%
“…Ozone damages four polypeptide chains on viral capsid proteins, damages RNA, disrupts the reproductive cycle, and inhibits viral replication 76 . However, ozone has been shown to oxidise intracellular cysteine residues 77 . The NOD‐like receptor family pyrin domain‐containing 3 (NLRP3) inflammasome is a cytoplasmic complex responsible for the production of IL‐1β and IL‐18 and plays a vital role in initiating inflammatory processes, including viral infections.…”
Section: Molecular Biological Mechanism Of Ozone Therapy For Cutaneou...mentioning
confidence: 99%
“… 76 However, ozone has been shown to oxidise intracellular cysteine residues. 77 The NOD‐like receptor family pyrin domain‐containing 3 (NLRP3) inflammasome is a cytoplasmic complex responsible for the production of IL‐1β and IL‐18 and plays a vital role in initiating inflammatory processes, including viral infections. Reportedly, ozone exhibits anti‐inflammatory activity by modulating the NLRP3 inflammasome.…”
Section: Molecular Biological Mechanism Of Ozone Therapy For Cutaneou...mentioning
confidence: 99%